2021
DOI: 10.1021/acsami.1c11730
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Active Sites of Gold-Cuprous Oxide Catalysts for Electrocatalytic Oxygen Reduction Reaction

Abstract: Understanding how the catalyst morphology influences surface sites is crucial for designing active and stable catalysts and electrocatalysts. We here report a new approach to this understanding by decorating gold (Au) nanoparticles on the surface of cuprous oxides (Cu2O) with three different shape morphologies (spheres, cubes, and petals). The Au-Cu2O particles are dispersed onto carbon nanotube (CNT) matrix with high surface area, stability, and conductivity for oxygen reduction reaction. A clear morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…2d). 41,42 This confirms that all the prepared samples have a pure chemical composition. Such an inference can also be verified by the high-resolution O 1s spectrum of both samples (Fig.…”
Section: Resultssupporting
confidence: 67%
“…2d). 41,42 This confirms that all the prepared samples have a pure chemical composition. Such an inference can also be verified by the high-resolution O 1s spectrum of both samples (Fig.…”
Section: Resultssupporting
confidence: 67%
“…Besides, some intermediate products like CO groups, such as ‐CO ads , ‐HCHO ads , and ‐HCOOH ads and so on, will be generated during ORR processes on the electrode surface of Pt‐based catalysts, and be adsorbed on catalyst surface, thereby leading to the poisoning of Pt‐based catalysts and the degradation of catalytic activity [52,53] . Therefore, the two crucial factors, those are durability and methanol crossover effect of Pt‐based electrocatalysts, are severely limiting the wide industrial application of fuel cells, especially for the direct methanol fuel cells (DMFCs) [54] . It is of great significance to develop non‐precious metal catalysts with outstanding resistance to methanol toxicity [55] .…”
Section: Resultsmentioning
confidence: 99%
“…To improve the number of surface-active sites, stability and conduction for oxygen reduction reaction as-developed Au−Cu 2 O catalysts were dispersed over carbon nanotubes. 200 The electrocatalytic investigations have revealed the morphology dependent improved ORR activity of the catalyst. It was observed that the deposited Au showed different oxidation states in morphologically different Cu 2 O catalysts.…”
Section: Effect Of Structural Features On Catalyticmentioning
confidence: 99%
“…To investigate this fact, Zhang et al have developed a Au deposited Cu 2 O catalyst having different morphologies like petals, cubes, and spheres. To improve the number of surface-active sites, stability and conduction for oxygen reduction reaction as-developed Au–Cu 2 O catalysts were dispersed over carbon nanotubes . The electrocatalytic investigations have revealed the morphology dependent improved ORR activity of the catalyst.…”
Section: Advances In Nanodimensional Metals and Metal Oxides As Catal...mentioning
confidence: 99%
See 1 more Smart Citation